Lemons and Leases in the Used Business Aircraft Market - Gilligan, Thomas W. (Journal of Political Economy, 2004)
Given adverse selection, durable goods that trade less frequently depreciate more quickly. Consistent with this prediction, I find an inverse relationship between depreciation and trading volume for less reliable brands of used business aircraft. Additionally, recent theoretical analyses suggest that leasing, by increasing the average quality of used goods offered for sale, may reduce adverse selection in durable goods markets. Indeed, I find an increase in the direct relationship between depreciation and trading volume for aircraft models with relatively high lease rates. Together these findings suggest that adverse selection is a prominent feature of the market for contemporary used business aircraft and that leasing mitigates the consequences of asymmetric information about the quality of used durable goods.